2020
DOI: 10.1016/j.jes.2020.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Vertical profiles of biogenic volatile organic compounds as observed online at a tower in Beijing

Abstract: Vertical profiles of isoprene and monoterpenes were measured by a proton transfer reaction-time of flight-mass spectrometry (PTR-ToF-MS) at heights of 3, 15, 32, 64, and 102 m above the ground on the Institute of Atmospheric Physics (IAP) tower in central Beijing during the winter of 2016 and the summer of 2017. Isoprene mixing ratios were larger in summer due to much stronger local emissions whereas monoterpenes were lower in summer due largely to their consumption by much higher levels of ozone. Isoprene mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 73 publications
(68 reference statements)
1
23
0
Order By: Relevance
“…The monoterpenes in particular showed a much stronger correlation with CO during the post-monsoon period suggesting an anthropogenic source. 30,59,72 This conclusion is similar to that reported by who suggested that biogenic molecules may be explained by vehicular or burning sources in Delhi. 45 Pre-monsoon campaign Post-monsoon campaign .…”
Section: Regression Analysissupporting
confidence: 88%
“…The monoterpenes in particular showed a much stronger correlation with CO during the post-monsoon period suggesting an anthropogenic source. 30,59,72 This conclusion is similar to that reported by who suggested that biogenic molecules may be explained by vehicular or burning sources in Delhi. 45 Pre-monsoon campaign Post-monsoon campaign .…”
Section: Regression Analysissupporting
confidence: 88%
“…A proton transfer reaction time-of-flight mass spectrometer (PTR-ToF-MS; Ionicon Analytik GmbH, Innsbruck, Austria), which has time resolution of less than 1 s, is used to monitor the real-time mixing ratios of BVOCs inside the chamber. More detail descriptions about the determination of BVOCs by the PTR-ToF-MS can be found elsewhere (Wang et al, 2014;Huang et al, 2016;H. Zhang et al, 2020).…”
Section: Design Of the Semi-open Dynamic Chamber Systemmentioning
confidence: 99%
“…Due to vital roles played by BVOCs in atmospheric chemistry, their emission inventory has become an indispensable part of air quality and climate models. Global annual emissions of BVOCs are estimated over 1 Pg (10 15 g) (Guenther et al, 1995), yet these estimations may have large uncertainties (Simpson et al, 1999;Guenther et al, 2006;Y. Zhang et al, 2020) and inaccurate emission factors are among the most important contributors to the uncertainties either regionally or globally (Wang et al, 2011;Guenther et al, 2012;Situ et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Acetonitrile is widely used as a typical tracer of biomass burning sources in previous studies (de Gouw et al, 2003;Zhang et al, 2020;Tan et al, 2021). However, biomass burning source was not identified in this study because acetonitrile was not predominantly attributed to a single factor (Figure 8).…”
Section: Source Analysis Of Vocs Measurementsmentioning
confidence: 83%